2021
DOI: 10.3389/fmicb.2021.678537
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Hepatitis B Virus Infection: A Multi-Faceted Player for Hepatocarcinogenesis

Abstract: Hepatitis B virus (HBV) infection has a multi-dimensional effect on the host, which not only alters the dynamics of immune response but also persists in the hepatocytes to predispose oncogenic factors. The virus exists in multiple forms of which the nuclear localized covalently closed circular DNA (cccDNA) is the most stable and the primary reason for viral persistence even after clearance of surface antigen and viral DNA. The second reason is the existence of pregenomic RNA (pgRNA) containing virion particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 161 publications
0
13
0
Order By: Relevance
“…One of the patients experienced a partial recovery that lasted for 27.7 months. Importantly, following HBV-TCR-T cell infusion, the majority of the patients showed a decrease in circulating HBsAg and HBV DNA levels or their stability, demonstrating on-target effects [18]. In another phase I clinical trial (NCT04677088), autologous T cells that expressed specific TCRs encoded by the incorporation of HBV-DNA into the host DNA were introduced.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the patients experienced a partial recovery that lasted for 27.7 months. Importantly, following HBV-TCR-T cell infusion, the majority of the patients showed a decrease in circulating HBsAg and HBV DNA levels or their stability, demonstrating on-target effects [18]. In another phase I clinical trial (NCT04677088), autologous T cells that expressed specific TCRs encoded by the incorporation of HBV-DNA into the host DNA were introduced.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…When HBsAg‐CART cells were adoptively transferred into HBV‐infected humanized mice, the levels of HBsAg and HBV‐DNA in the liver significantly dropped in comparison with those in control animals. Notably, after treatment with HBsAg‐specific CAR‐T cells, the proportion of HBV core–positive hepatocytes among all human hepatocytes significantly decreased, suggesting noncytopathic viral elimination [18].…”
Section: Studies Of Oncogenic Viral Antigen–specific Engineered T Cel...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is di cult for patients with high baseline HBsAg to achieve clinical cure, the decrease of HBsAg is helpful to reduce the occurrence of liver cirrhosis and liver cancer to a certain extent. A retrospective study conducted in Taiwan, China, showed that patients treated with peginterferon had a lower incidence of hepatocellular carcinoma (HCC) than those treated with nucleoside (acid) analogues (P = 0.011) [14].Studies have shown that long-term exposure to HBsAg in the circulation can lead to an imbalance of immune response, thus forming an immune tolerance microenvironment, and thus promoting tumor progression [15].…”
Section: Clinical Curementioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is a common cause of cancer-related mortality and morbidity worldwide (Shah, et al 2022, Sung, et al 2021). Multiple studies have shown that the main risk factors for HCC are chronic hepatitis B and C virus infections, alcohol abuse, and obesity (Ghosh, et al 2021, Iannacone and Guidotti 2022, Konyn, et al 2021, Nabih 2020, Villanueva 2019). The disease burden is signi cantly higher when a combination of HCC and nonalcoholic fatty liver disease (NAFLD) is seen, a common occurrence due to the current obesity epidemic (Ahmad, et al 2022, Villanueva 2019).…”
Section: Introductionmentioning
confidence: 99%